Studi fenomenologi: Memaknai aktivitas dog walking sebagai fungsi rekreasi - Risa Juliadilla (Jurnal Psikologi Tabularasa, 2021)
Dog walking provides double-positive impacts to the owner and its dog both psychologically and physically. Dog walking with the aim of recreational activity can accommodate the dog owners and their pets with the good involvement that can perform as therapeutic to reduce stress. The research is qualitative within the perspective of phenomenology. The research question is how the pet owners understand dog walking as a recreational activity? This research aims to provide the reference on the Human-Animal Interaction implementation with the scope of psychology. Dog walking becomes a fun activity for the owner and performs proper stress relief. Dog walking for the pet owners is a sense to interact and communicate with their pets.